2009
DOI: 10.1159/000245916
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Horse Chromosome 5q in the Genus <i>Equus</i> and Centromere Repositioning

Abstract: Horses, asses and zebras belong to the genus Equus and are the only extant species of the family Equidae in the order Perissodactyla. In a previous work we demonstrated that a key factor in the rapid karyotypic evolution of this genus was evolutionary centromere repositioning, that is, the shift of the centromeric function to a new position without alteration of the order of markers along the chromosome. In search of previously undiscovered evolutionarily new centromeres, we traced the phylogeny of horse chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…Cross-species chromosome painting has confirmed the great karyotypic variability of this genus [19]. In addition, we have shown that at least nine centromere repositioning events took place during the evolution of this genus, six of which occurred in E. asinus (donkey) [12],[20] and one of which occurred in horse chromosome 11 (ECA 11). These results demonstrate that the phenomenon of centromere repositioning played a key role in the rapid karyotypic evolution of the equids and point to these species as an ideal model system for the analysis of neocentromere formation and centromere evolution.…”
Section: Introductionmentioning
confidence: 56%
“…Cross-species chromosome painting has confirmed the great karyotypic variability of this genus [19]. In addition, we have shown that at least nine centromere repositioning events took place during the evolution of this genus, six of which occurred in E. asinus (donkey) [12],[20] and one of which occurred in horse chromosome 11 (ECA 11). These results demonstrate that the phenomenon of centromere repositioning played a key role in the rapid karyotypic evolution of the equids and point to these species as an ideal model system for the analysis of neocentromere formation and centromere evolution.…”
Section: Introductionmentioning
confidence: 56%
“…It is worth noting that the centromere of horse chromosome 11 lacks any satellite DNA, as it was demonstrated in our previous horse genome sequencing work [Wade et al, 2009]. The absence of FISH-detectable 37cen and 2PI signals from the centromere of several domestic donkey, Grevy's zebra and Burchelli's zebra chromosomes [Piras et al, 2009[Piras et al, , 2010 raises the question whether satellite DNA, belonging to other families, might be present at such centromeres. To investigate this possibility, we performed FISH analyses on the chromosomes of the 4 species, using their total genomic DNA as probe [Piras et al, 2010].…”
mentioning
confidence: 70%
“…Still, it must be taken into account that a very small amount of the 37cen satellite, under the resolution level of FISH analysis, may be present. Moreover, we want to stress that in the horse (ECA11cen), and presumably in the domestic donkey and in the zebras, satellite-free centromeres exist [Wade et al, 2009;Piras et al, 2009Piras et al, , 2010; therefore, it cannot be ruled out that key single copy sequences could play a role in centromere function also in some satellite-positive centromeres.…”
Section: High-resolution Analysis Of Horse Satellite Dna Organizationmentioning
confidence: 99%
“…Other sites have been identified on ECA 1 and ECA 16 that appear to be fragile and potentially predisposed to rearrangement (Lear et al 2008). Further investigation revealed repositioned centromeres in the donkey and one species of zebra, further defining the evolutionary relationship between species within this genus (Piras et al 2009; Piras. et al 2010).…”
Section: A Brief History Of Horse Genome Researchmentioning
confidence: 89%
“…Diploid chromosome numbers within the genus range from 32 to 66 (Piras et al 2009) in the mountain zebra and Przewalski’s horse respectively; the domestic horse has a diploid number of 64. An “evolutionary new centromere” was identified on equine chromosome 11 (ECA 11) in a region highly conserved across mammalian species, with the horse being the only mammal known to possess a centromere in this location (Wade et al 2009).…”
Section: A Brief History Of Horse Genome Researchmentioning
confidence: 99%